Polish support for refugees from Ukraine in the face of war in 2022 - selected aspects - Sabina Grabowska; Anna Pięta-Szawara (Journal of Modern Science, 2023)
Objectives The purpose of the article is to analyze the Polish policy towards refugees from Ukraine after February 24, 2022, including indicating actions taken to them by society, non -governmental organizations, local governments and state central bodies. Attention was paid to the social, economic and cultural aspects of migration, as well as the possible scenarios of the development of the situation, depending primarily on the development of the conflict in Ukraine.